Development of a sustainable, simple, and robust method for efficient l-DOPA extraction - Polanowska, Katarzyna (2020)
ABSTRACT: l-3,4-dihydroxyphenylalanine (l-DOPA) is a medically relevant compound in Parkinson's disease therapy. Several extraction methods of l-DOPA from beans, including velvet and faba beans, have been described in the literature. However, these methods require the use of strong acids, long extraction times, or complex downstream processing, which makes the extraction of l-DOPA expensive and energy-demanding, limiting its industrial application. In addition, the stability of l-DOPA during the extraction process is critical, further complicating the extraction of adequate amounts of this amino acid. This work is the first report on a simple, rapid, greener, and robust extraction method of l-DOPA. The developed method consists of a quick homogenization step followed by a double extraction with 0.2% v/v acetic acid for 20 min and was applied to faba bean at a ratio of 1:25 with respect to the extracting solvent. This study also investigated the stability of l-DOPA during extraction and thermal treatment. The proposed method demonstrated to be robust and extraordinarily efficient for numerous cultivars of faba bean, velvet bean, and food products containing faba beans.